Organization of stage rehabilitation of servicemen with gunshot defects of soft tissues at the levels of medical care - Babov, K.D.; Khomenko, I.P.; Tertyshnyi , S.V.; Babova I.K., Babova I.K.; Vastianov , R.S. (Medicni Perspektivi, 2021)
Building a modern system of rehabilitation of servicemen in Ukraine is an integral part of providing medical care in armed conflict. Rehabilitation of servicemen after gunshot wounds with soft tissue defects of the lower extremities is a common but difficult problem for surgical and rehabilitation teams. The process of rehabilitation requires the implementation of certain methodological provisions. At present, medical care for servicemen is a four-levels’ one. Rehabilitation service is provided at the third and fourth levels of medical care. The aim of the study was to improve the quality of medical care for servicemen after gunshot wounds with soft tissue defects of the lower extremities by introducing a system of staged rehabilitation. Organizational and methodological bases of the system of staged rehabilitation of wounded servicemen with soft tissue defects at different levels of medical care have been developed. Two models of rehabilitation depending on the severity of the injury and the tactics of surgical treatment are proposed. The division of the stage of early sanatorium rehabilitation for the wounded with severe soft tissue injuries depending on the stage of surgical treatment and the formation of a "skin patch" is justified. The introduction of the proposed models of rehabilitation of wounded with soft tissue defects in the practice of early sanatorium rehabilitation will provide increasing of medical care quality.